Synthesis of Hierarchical ZSM‐11 Nanorods Aggregates and Catalytic Properties in Cyclohexene Hydration to Cyclohexanol. Issue 4 (26th January 2023) - Yang, Mengyao; Wang, Yaquan; Liu, Wenrong; Lu, Jiaxin; Shi, Mingxue; Wu, Shuhui; Bu, Lingzhen; Zhi, Yaqiong; Wang, Zhiqiang; Sang, Juncai; Chu, Kailiang; Huang, Yitong; et al.
Abstract: A series of hierarchical ZSM‐11 nanorods aggregates were prepared by a hydrothermal crystallization method with the addition of cetyltrimethylammonium bromide (CTAB). The physical and chemical properties of the samples were characterized and the catalytic properties in the direct hydration of cyclohexene to cyclohexanol were also investigated. The characterization results showed that adding CTAB effectively increased the crystallinity of the zeolite, and the external specific surface areas and pore volume of the zeolite increased dramatically. With the increase of CTAB addition, more and more mesopores were formed which could be clearly seen from TEM micrograph. The ratio of Brønsted/Lewis acid decreased first and then increased with the increase of CTAB addition, with the lowest point appeared at the ratio of CTAB/SiO2 of 0.015. The zeolite synthesized at the CTAB/SiO2 ratio of 0.015 exhibited the highest reaction rate with the cyclohexene conversion as high as 14.23 %. The excellent performance of the hierarchical ZSM‐11 nanorods aggregates can be attributed to the lowest Brønsted/Lewis acid ratio and large mesoporous volume. Abstract : Hierarchical ZSM‐11 nanorods aggregates with external specific surface areas and mesoporous volumes were synthesized by hydrothermal crystallization with the addition of hexadecyltrimethylammonium bromide (CTAB). The catalytic performance of the catalyst for the reaction of cyclohexene hydration to cyclohexanol was tested. The nanorods aggregates showed a significant increase in the conversion of cyclohexene.